Perovskite chromates cathode with resolved and anchored nickel nano-particles for direct high-temperature steam electrolysis - Xu, S.; Dong, Dehua; Wang, Y.; Doherty, W.; Xie, K.; Wu, Y. (Elsevier SA, 2013)
Doped lanthanum chromates are now commonly used to prepare composite cathodes for direct steam electrolysis. However, the limitation of electrochemical performances and cell current efficiency by insufficient electro-catalytic activity is a major challenge. This paper reports the use of reversibly exsolved catalytic metallic Ni nano-particles on A-site deficient and B-site excess perovskite (La0.75Sr0.25)0.95(Cr0.8Ni0.2)0.95Ni0.05O3-delta (LSCNNi), in order to achieve an activity-enhanced composite cathode via high-temperature reduction under reducing atmospheres. The electrical properties of the ceramic are investigated methodically and correlated with the performances of the composite electrodes in symmetric and electrolysis cells. XRD, SEM, EDS and XPS results, confirm that the exsolution or dissolution of nano metallic catalyst is reversible in redox treatment cycles. The Faradic efficiency reaches approximately 80% for the LSCNNi cathode with the flow of 5%H2/Ar. Ultimately, the unified effect of metallic catalyst and redox-stable ceramic produce striking redox stability as well as electrochemical performances of the titled composite cathode. The results signify that the composite cathode with exsolved nickel nano-particles, is a good potential fuel electrode for direct steam electrolysis in an oxygen-ion conducting solid oxide electrolyzer.